Renditions of national teams on wrestling on the World Cup of 2016 - Vladimir Shatskikh; Viktor Ezan; Viktor Ponomaryov; Oleg Klimenko (Kharkiv State Academy of Physical Culture, 2016)
Purpose: to carry out the analysis of renditions of national teams on wrestling on the World Cup of 2016. Material & Methods: the analysis of 328 fights of highly skilled wrestlers is carried out. Results: it is determined that the advantage of the strongest wrestlers consists in successful and stable use of technical-tactical actions near other factors during a duel meet and ability to impose to the rival the style of conducting a fight. Conclusions: it is established that the offensive actions prevail as a part of the competitive technique, the fight is conducted constantly at high speed, and the techniques are carried out after the previous preparation, and in case the sportsmen is sure that the technique will be executed.